Challenges for the Italian Public Health Genomics Task Force (Italian Journal of Public Health, 2006)
Dear Sirs,In recent years, the results of the Human Genome Project have lead to huge expectations relating to the rapid implementation of its results in the field of prevention.The possibility to provide early detection for those individuals more susceptible to complex diseases, because of their genetic make-up, might theoretically result in individualized primary (e.g., chemoprevention) and secondary prevention (e.g., assiduous monitoring) programs.The issue of an individuals inherited susceptibility to develop complex diseases, however, is much more complicated than it first appears, because of the delicate links between scientific developments, technical applications and ethical considerations. Consequently, besides the framework required for the critical evaluation of genetic testing (analytical validity, clinical validity and clinical utility of the test),we must also consider these three fundamental aspects: • From pooled and meta-analyses of genetic association studies, it appears that most of the commonly identified genetic variants (polymorphisms) confers a low risk of disease (on average ORs of 1.5, if not lower), which only increases with the interaction of well-known environmental risk factors• From preliminary studies, the result from a ‘positive’ genetic testing does not seem to motivate behavioural changes;• There is a need for an evidence-based approach to genetic testing that integrates the cost-utility evaluation of each available genetic test [Health Technology Assessment (HTA) framework] while considering the weight of the relevant ethical issues.